Analisa Manajemen Syariah dalam Pengelolaan Bantuan Langsung Tunai Dana Desa terhadap Kesejahteraan Masyarakat pada Masa Covid-19 di Kecamatan Gerung Kabupaten Lombok Barat - L. Bagus Prihatin Wicaksananta; Bq. Ratna Mulhimah; H. Ahmad Amir Aziz (LP2M STIT Palapa Nusantara, 2023)
The social and economic impacts caused by the Covid-19 pandemic are in fact very influential on the level of social welfare, including causing many people to lose their jobs so that it has the potential to increase the number of poor people. When the economy is weakening due to Covid-19, the only thing that can be expected is financial stimulus, which is government policy. The Village Fund Direct Cash Assistance Program (BLT-DD) is very helpful in encouraging public consumption. The aim of the study was to find out how far the Village Fund Direct Cash Assistance is managed and the impact of BLT-DD management on Community Welfare in Gerung District, West Lombok Regency. The type of research used is field research which is a research mechanism using area exploration which produces descriptive information, in written form or information by people by looking at the observed research. This research was conducted by collecting data in the form of observation data, questionnaires, interviews and documentation. The research locations were taken by researchers in three villages namely: (a). Tempos Village; (b). Kebon Ayu Village; (c). Suka Makmur Village. The results of this study indicate that First, Direct Cash Assistance to Village Funds in terms of Identification of Beneficiary Groups is still weak, this is evidenced by the discrepancy in the distribution of Village Fund BLT at least 40% of Village Funds so that the number of KPM social assistance is reduced than it should be; Second. Management of Village Fund BLT distribution to poor families in villages in the form of targeting accuracy, there are still duplication of KPM recipients of Village Fund BLT who also receive other social assistance such as PKH and BPNT; Third, there are problems with receiving multiple NIK Village Fund BLT or invalid NIK; Fourth, there are reports from the public regarding the management of the BLT Dana Desa in 2021 in which the KPM is rotated to receive non-permanent social assistance for a year. For now, the distribution of Village Fund Direct Cash Assistance in the three villages has been running until the fourth quarter, namely January to December 2022; Fifth, the positive impact of the Village Fund Direct Cash Assistance program can help the community's economy, including increasing the purchasing power of people affected by Covid-19.